2019
DOI: 10.1016/j.juro.2018.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Higher Neural Correlates in Patients with Multiple Sclerosis and Neurogenic Overactive Bladder Following Treatment with Intradetrusor Injection of OnabotulinumtoxinA

Abstract: Intradetrusor injection of OnabotA appears to increase the activity most of the brain regions known to be involved in the sensation and process of urinary urgency in female MS patients with NOAB. This is the first study of its kind to evaluate the possible effects of OnabotA at the human brain level where sensory awareness is located. This pattern of activation may be used to phenotype patients further to optimize therapy or to uncover sensory effects of OnabotA beyond the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Using a region‐of‐interest based analysis of the pons in 42 MS‐patients, Weissbart et al found associations between the pontine lesion volume and lower urinary tract symptoms. Khavari et al demonstrated diverging cerebral activation patterns in functional MRI in MS‐patients with urinary dysfunction compared with controls . Functional imaging revealed activation of areas involved in the micturition cycle like the frontal lobe, cingulate gyrus, and basal ganglia in these patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a region‐of‐interest based analysis of the pons in 42 MS‐patients, Weissbart et al found associations between the pontine lesion volume and lower urinary tract symptoms. Khavari et al demonstrated diverging cerebral activation patterns in functional MRI in MS‐patients with urinary dysfunction compared with controls . Functional imaging revealed activation of areas involved in the micturition cycle like the frontal lobe, cingulate gyrus, and basal ganglia in these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Functional imaging revealed activation of areas involved in the micturition cycle like the frontal lobe, cingulate gyrus, and basal ganglia in these patients . The use of botulinum toxin in overactive bladder treatment increased the activity of supraspinal centers known to be involved in bladder control in female MS‐patients with urinary dysfunction . However, especially the role and patterns of supratentorial lesions in the pathogenesis of urinary incontinence in MS remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent breakthrough study using concurrent functional magnetic resonance imaging (fMRI) and urodynamic studies in female patients with multiple sclerosis and neurogenic overactive bladders reported that an intradetrusor injection of BTX-A increased the activity of most brain regions (cingulate body, prefrontal cortex, insula, and pontine micturition center) involved in the sensation and process of urinary urgency [86]. This was a pilot study to evaluate the possible effects of BTX-A at the level of the brain where sensory awareness is located.…”
Section: Btx Effects In Central Nervous Systemmentioning
confidence: 99%
“…A recent study of patients with neurogenic DO secondary to MS undergoing intravesical BTX-A treatment has demonstrated the potential of fMRI to phenotype patients and optimise therapy based upon baseline activation patterns (40), but whether this tool can also be used to predict outcome from BTX-A treatment for idiopathic OAB remains to be determined.…”
Section: The Role Of Functional Mrimentioning
confidence: 99%